Effects of repetitive transcranial magnetic stimulation on inhibitory control in first-episode schizophrenia: behavioral and neural mechanisms - Yu, Sihang; Wang, Shuai; Sun, Hang (Frontiers in Psychiatry, 2024)
BackgroundInhibitory control deficits are a core feature of cognitive impairment in schizophrenia, associated with abnormal activation of key brain networks. Repetitive transcranial magnetic stimulation (rTMS) targeting the dorsolateral prefrontal cortex (DLPFC) may help improve inhibitory control, but its specific effects in schizophrenia remain uncertain.MethodsThis study involved 150 participants divided into Real-rTMS, Sham-rTMS, and healthy control groups. Inhibitory control was assessed using the dual-choice oddball task, and task-based functional magnetic resonance imaging (fMRI) was employed to examine neural activity. The Real-rTMS group received active stimulation over the DLPFC, and the Sham group received placebo stimulation.ResultsThe Real-rTMS group exhibited significant improvements in both reaction times and accuracy compared to the Sham group, indicating enhanced inhibitory control. fMRI data showed that brain activity in regions such as the cerebellum, insula, thalamus, and prefrontal cortex was normalized in the Real-rTMS group, with activation patterns closely resembling those observed in healthy controls. Additionally, task-based fMRI revealed a restoration and further enhancement of negative activation in regions like the middle frontal gyrus and superior temporal gyrus, which helped reduce cognitive interference from irrelevant stimuli.ConclusionrTMS targeting the DLPFC improves inhibitory control in schizophrenia by modulating both positive and negative brain activation patterns. These findings highlight the dual mechanism through which rTMS enhances cognitive control, offering a promising intervention for cognitive deficits in schizophrenia. Future research should explore the long-term effects of this modulation on broader cognitive functions.